Who speaks for Islam? : what a billion Muslims really think - Esposito, John L.; Mogahed, Dalia (New York, NY : Gallup Press, 2007)
Draws on in-depth research to offer insights into what Muslims actually believe about key global issues such as democracy, radicalism, and women's rights, in an account that seeks to differentiate extremists from everyday Muslims.
Introduction: Islam's Silenced Majority -- Ch. 1. Who Are Muslims? -- Ch. 2. Democracy or Theocracy? -- Ch. 3. What Makes a Radical? -- Ch. 4. What Do Women Want? -- Ch. 5. Clash or Coexistence? -- App. A. Methodological Design and Sampling -- App. B. The Gallup Journey to Poll the World.
"Based on Gallup's world poll -- the largest study of its kind."
Includes bibliographical references (pages [185]-204).
Karim International
Keywords: Islam -- 21st century; Islam -- Relations; English language